2015
DOI: 10.1177/1471301215623889
|View full text |Cite
|
Sign up to set email alerts
|

‘The nourishing soil of the soul’: The role of horticultural therapy in promoting well-being in community-dwelling people with dementia

Abstract: Two-thirds of people with dementia reside in their own homes; however, support for community-dwelling people with dementia to continue to participate in everyday activities is often lacking, resulting in feelings of depression and isolation among people living with the condition. Engagement in outdoor activities such as gardening can potentially counteract these negative experiences by enabling people with dementia to interact with nature, helping to improve their physical and psychological well-being. Additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 43 publications
1
22
0
2
Order By: Relevance
“…Some of the differences between those approaches are in the level of care and therapy provided [ 16 ]. Those interventions done within structured rehabilitation or health programs with clearly defined patient-orientated goals are commonly defined with the terms therapy or care such as therapeutic horticulture, therapeutic gardening or care farming [ 67 ]. In care farming and social farming the objectives are more related to conducting meaningful occupational activities and achieving employment goals at real production and commercial farms [ 40 ] and especially within social farming the therapeutic intent is not so explicit, with the aim being to promote innovation and collaboration pathways between sectors in local communities following social and employment inclusion and integration principles [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the differences between those approaches are in the level of care and therapy provided [ 16 ]. Those interventions done within structured rehabilitation or health programs with clearly defined patient-orientated goals are commonly defined with the terms therapy or care such as therapeutic horticulture, therapeutic gardening or care farming [ 67 ]. In care farming and social farming the objectives are more related to conducting meaningful occupational activities and achieving employment goals at real production and commercial farms [ 40 ] and especially within social farming the therapeutic intent is not so explicit, with the aim being to promote innovation and collaboration pathways between sectors in local communities following social and employment inclusion and integration principles [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the core objectives of HT is to promote social support and sharing amongst the participants. Noone et al (2015) demonstrated that communal gardening with its collaborative features, may instil a sense of belonging to the community, hence improving social integration [11]. …”
Section: Introductionmentioning
confidence: 99%
“…Gardening can provide significant benefits to mental health (Quick et al, 2017). It can also improve physical and psychological wellbeing, reduce social isolation, reduce anxiety, and depression (Noone et al, 2017). In addition to improving mental health and physical health, gardening can also improve cognitive function (Chan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%